Effect of family-centered empowerment model on self-efficacy in patients with obsessive compulsive disorder: A quasi-experimental study (Bangladesh Journal of Medical Science, 2021)
Objective: Obsessive compulsive disorder is one of the most common disorders affectig the individuals’ performance. Promotion of self-efficacy is important in these patients. This study determined the impact of family-centered empowerment model on self-efficacy in patients with obsessive compulsive disorder.Material and Methods: This was a quasi-experimental single group before-after intervention study, which conducted on 36 patients with Obsessive compulsive disorder. The samples were selected with purposive sampling method using inclusion criteria. The family-centered empowerment model was implemented in 5 sessions for 3 months focusing on four categories (perceived threat, self-efficacy, educational contribution, and assessment). The instrument used consisted of two parts including demographic information questionnaire and Self-efficacy Questionnaire which was completed before, immediately after, and 1.5 month after intervention by the study units. The data were analyzed with SPSS21 using descriptive Statistics, repeated measure ANOVA and paired t-test.Results: The mean selfefficacy scores were 47.78±8.71 and 51.44±10.83 before and after intervention, respectively (P=0.04). Also, a comparison of self-efficacy scores with t-test before and after intervention and follow-up indicated a significant correlation (P